2020
DOI: 10.1021/acs.jchemed.0c01074
|View full text |Cite
|
Sign up to set email alerts
|

Beneath the Surface: An Investigation of General Chemistry Students’ Study Skills to Predict Course Outcomes

Abstract: As the conversation in higher education shifts from diversity to inclusion, the attrition rates of students in the STEM fields continue to be a point of discussion. Combined with the demand for expansion in the STEM workforce, various retention reforms have been proposed, implemented, and in some cases integrated into policy following evidence of success. Still, new findings, technological advances, and socio-cultural shifts inevitably necessitate an ongoing investigation as to how students approach learning. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…First, academic and family backgrounds have been pointed out as key factors in determining students’ success in college, especially in gateway courses such as general chemistry. In the context of characterizing academically successful and “at risk” students in chemistry classes, studies have reported that Piagetian formal thought ability and SAT scores can predict students’ performance in General Chemistry I , and that students who use a surface learning approach are less likely to succeed in general chemistry than those who use a deep learning approach . In a study conducted in Germany, Rüschenpöhler and Markic showed that students with higher levels of chemistry capital (resources that aid success in chemistry, such as parents knowledgeable in chemistry) were more likely to be represented in higher track classes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, academic and family backgrounds have been pointed out as key factors in determining students’ success in college, especially in gateway courses such as general chemistry. In the context of characterizing academically successful and “at risk” students in chemistry classes, studies have reported that Piagetian formal thought ability and SAT scores can predict students’ performance in General Chemistry I , and that students who use a surface learning approach are less likely to succeed in general chemistry than those who use a deep learning approach . In a study conducted in Germany, Rüschenpöhler and Markic showed that students with higher levels of chemistry capital (resources that aid success in chemistry, such as parents knowledgeable in chemistry) were more likely to be represented in higher track classes.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of characterizing academically successful and "at risk" students in chemistry classes, studies have reported that Piagetian formal thought ability and SAT scores can predict students' performance in General Chemistry I 27,28 and that students who use a surface learning approach are less likely to succeed in general chemistry than those who use a deep learning approach. 29 In a study conducted in Germany, Ruschenpoḧler and Markic 30 showed that students with higher levels of chemistry capital (resources that aid success in chemistry, such as parents knowledgeable in chemistry) were more likely to be represented in higher track classes. During the time of the COVID-19 pandemic, the effects of differences in students' family backgrounds were even further exacerbated because many students of marginalized backgrounds also needed to manage family responsibilities and had limited access to adequate technology and space for studying.…”
Section: Current Explanations Of Existing Inequitiesmentioning
confidence: 99%
“…A challenging class might be a good training ground for students, since most of the students enrolled will require help to master the material and might therefore have an open mind to interventions that modify their study habits. Specific activities designed to increase the students’ metacognitive abilities in chemistry courses offer a path for students to be intentionally reflective, and to improve their performance in courses that could otherwise hinder their ability to complete their degree programs. , …”
Section: Introductionmentioning
confidence: 99%
“…examined the resources used by students in general chemistry and found that higher-ability students strategically matched the study resource to the assessment type more often than lower-ability students . Recent research on predicting students’ odds of success based on their study approaches found two distinct sets of lower-performing students; one aligned with surface approaches to learning and the other to both deep and surface approaches to learning . A deep approach involves learners who demonstrate intrinsic motivation and a determination to understand the meaning of learning material.…”
mentioning
confidence: 99%
“…14 Recent research on predicting students' odds of success based on their study approaches found two distinct sets of lowerperforming students; one aligned with surface approaches to learning and the other to both deep and surface approaches to learning. 15 A deep approach involves learners who demonstrate intrinsic motivation and a determination to understand the meaning of learning material. A surface approach is more associated with extrinsic motivation and a focus on memorization of facts and processes.…”
mentioning
confidence: 99%